Pengaruh Kelas Balita Girang terhadap Peningkatan Status Gizi pada Balita Gizi Kurang, Buruk Dan Stunting - Nilatul Izah; Meyliya Qudriani; Laduniyah Furqoni (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2022)
The fulfillment of proper, complete and balanced nutrition in infants under the age of five years (toddlers) can have an influence on the growth and development of children as a whole. The most common problem related to the fulfillment of toddler nutrition is the lack of protein energy. Classification in toddlers includes: stunting (short body), thin, and poor nutrition. This study is a quantitative study with the aim of knowing the effect of the class of excited toddlers on the incidence of stunting in the Kramat Village area, Tegal Regency, the approach used in this study was Cross Sectional. The population in this study were all children under five, whether or not participating in the class activities of happy toddlers in the Kramat Public Health Center, Tegal Regency. The samples in this study were 64 people/toddlers. The results showed that the incidence of stunting decreased after the activity of the happy toddler class, based on the t test results showed that there was an influence between the excited toddler class and stunting status in toddlers with a p value of 0.009.